The Effects of Tip Recommendations on Customer Tipping, Satisfaction, Repatronage, and Spending - Alexander, Damon; Boone, Christopher; Lynn, Michael (Management Science, 2021)
A field experiment involving 94,571 orders from 24,637 customers of an app-based laundry pick-up, cleaning, and delivery service examined the effects of various randomly assigned tip recommendations on consumers’ tip amounts, satisfaction ratings, frequency of return, and bill size. We find that tip recommendations affect tip amounts, but not customer satisfaction, patronage frequency, or bill size, which implies that neither the processes underlying the tip-recommendation effects on tipping nor consumer tipping itself affect these other consumer outcomes. From a practical perspective, these results and conclusions inform efforts to increase or decrease tipping. Recommending larger tip amounts, at least within the 2–10 or 5%–25% ranges studied here, appears to be a safe means of increasing the amounts customers leave. More generally, altering customers’ tipping behavior will not itself adversely affect those customers’ subsequent satisfaction, repatronage, or spending, as long as the means used to alter tipping do not directly affect these other outcomes. This paper was accepted by John List, behavioral economics.